1973
DOI: 10.1037/h0034973
|View full text |Cite
|
Sign up to set email alerts
|

Durability of effects of group counseling with institutionalized delinquent females.

Abstract: A one-year follow-up revealed that the positive effects of group counseling with delinquents were still present on three of four concepts as measured by the semantic differential technique. In addition, significantly more of the experimental group had been released and not recommitted to the institution. Implications and the need for specific research are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Although authors of some dated studies have demonstrated improvement using RT (Persons, 1966;Redfering, 1972), many other researchers have found that relationshipbased therapy has little or no effect on problematic behaviors -even when assessed immediately posttreatment (Alexander & Parsons, 1973;Feldman, Caplinger, & Wodarski, 1983). Some suggest, when it comes to oppositional behaviors, the therapeutic relationship may be necessary but is insufficient by itself in effecting change (Alexander , Barton , & Schiaro, 1976).…”
mentioning
confidence: 99%
“…Although authors of some dated studies have demonstrated improvement using RT (Persons, 1966;Redfering, 1972), many other researchers have found that relationshipbased therapy has little or no effect on problematic behaviors -even when assessed immediately posttreatment (Alexander & Parsons, 1973;Feldman, Caplinger, & Wodarski, 1983). Some suggest, when it comes to oppositional behaviors, the therapeutic relationship may be necessary but is insufficient by itself in effecting change (Alexander , Barton , & Schiaro, 1976).…”
mentioning
confidence: 99%
“…Treatment is designed to provide a corrective emotional experience and to permit self-exploration and the expression of feelings (C. H. Patterson, 1979;Reisman, 1973). Although some studies of client-centered therapy, provided individually or in groups, have improved in adjustment among antisocial delinquent youths (e.g., Persons, 1966;Redfering, 1973), other studies have shown little or no change (Alexander & Parsons, 1973;Feldman, Caplingen & Wodarski, 1983). In a prior study of antisocial children, relationship therapy did not led to significant gains across a range of measures for antisocial children (Kazdin, Esveldt-Dawson, French, & Unis, 1987a).…”
mentioning
confidence: 99%
“…The compliance process was inherent in the situation chosen by Redfering (1971) to measure the effects of group counseling. His sub jects were a group of female delinquents who were confined in a correc tional institution.…”
Section: The Compliance Processmentioning
confidence: 99%